2006
DOI: 10.2495/geo060101
|View full text |Cite
|
Sign up to set email alerts
|

After treatment of landfill leachate in peat filters

Abstract: The main objective of this study was to determine the treatment capacity of well mineralised Sphagnum peat in order to reduce BOD and COD values and nutrient concentration in landfill leachate. The peat filters were suitable for the reduction (up to 93%) of ammonia nitrogen. Good results were obtained in the reduction of total phosphorus from both raw and pre-treated leachate (up to 81% and 70-99% respectively). The purification rate of the landfill leachate depended on the contamination rate-the outflow resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The result of the leachate analyses before and after treatment by the bio filter showed that, the concentrations were directly equal to the absorbance of the leachate samples, with that of the raw leachate being higher than the other leachate samples and this could be due to the absence of pre-treatment in the raw leachate. This phenomenon could be seen in another research by Kõiv et al, (2006) where, the purification NASIR, Z. J; MOHAMMED, S. S. D; MANGSE, G.…”
Section: Blast Samplementioning
confidence: 60%
“…The result of the leachate analyses before and after treatment by the bio filter showed that, the concentrations were directly equal to the absorbance of the leachate samples, with that of the raw leachate being higher than the other leachate samples and this could be due to the absence of pre-treatment in the raw leachate. This phenomenon could be seen in another research by Kõiv et al, (2006) where, the purification NASIR, Z. J; MOHAMMED, S. S. D; MANGSE, G.…”
Section: Blast Samplementioning
confidence: 60%